Enriching Students’ Vocabulary Mastery through English Spelling Bee Games - Putri Tria Pratiwi; Fera Zasrianita; Ali Akbarjono (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
This research aims to enriching students vocabulary mastery by using spelling bee games. The population of this research was the seventh grade students of SMP Negeri 15 Kota Bengkulu with consisted of 180 students into seven classes, namely VII A – VII F. After ensuring with the purposive sampling, two classes were finally chosen as the sample of this research: VII D as the experimental class and VII E as the control class. Both of classes consisted of 30 students with almost homogenous score. This research had been conducted at SMP Negeri 15 Kota Bengkulu. This research employed a Quasi-Experimental method. The Experimental class treated by using Spelling Bee strategy, while the control class was using the conventional ways. The pre-test was given to the two groups before giving the treatment. The result of pre-test showed the mean score of experimental class was 60.17 and the control class was 59.83. After giving the treatment, post-test was given. The result of post-test showed the mean score of experimental class was 76.00 and the control class was 69.83. in addition, the result of independent sample T-test (0.094) showed that t-count was smaller than t-table (2.00172) and sig (2-tailed) was higher than 0.05 (0.925 > 0.05). In other words, Ho was accepted and Ha was rejected. In summary, it could be stated that students’ who were taught vocabulary by using Spelling Bee was more effective than using the conventional ways. So, it can be concluded that Spelling Bee has positive effect to the Seventh Grade Students’ at SMP Negeri 15 Kota Bengkulu in vocabulary Mastery.